Managing Soil Carbon Sequestration: Assessing the Effects of Intermediate Crops, Crop Residue Removal, and Digestate Application on Swedish Arable Land - Sergio Alejandro Barrios Latorre; Lovisa Björnsson; Thomas Prade (GCB Bioenergy)
ABSTRACT Promoting the bioeconomy to aid in the achievement of sustainability goals has increased demand for biomass as feedstock. Residual biomass from agricultural production is an attractive option, as it is a by‐product that does not compete with food production. However, crop residues are important for the preservation of soil quality, especially for the maintenance of soil organic carbon. Therefore, their use can conflict with environmental goals and initiatives that aim to preserve soil fertility and carbon stocks. Nevertheless, the adoption of intermediate crops could compensate for the negative effects of crop residue removal. Moreover, if crop residues are used for a bioeconomy pathway such as biogas production, the resulting digestate derived from the anaerobic digestion process could be returned to the soil, providing an input of highly recalcitrant carbon. In this study, we modeled the effects of removal of crop residues, the cultivation of intermediate crops, and the application of digestate on Swedish soil organic carbon stocks. Our results suggest that the inclusion of intermediate crops could raise the carbon stocks at equilibrium by an average of 1.93 t C ha−1 (~3% increase) with a notable spatial variation. Digestate application showed a higher average increase (3.3 t C ha−1, ~5%) with an even higher variation. The removal of crop residues was detrimental in some areas, resulting in a loss of carbon, which could not be compensated for entirely by the introduction of intermediate crops or digestate recycling. Combining these two practices showed overall positive effects on soil organic carbon stocks; however, the results cannot be generalized at any spatial location, and we emphasize the importance of assessments tailored to local conditions.